Analisis Kesalahan Berbahasa Pada Teks Eksposisi Siswa Kelas X SMA Swasta Raksana Medan - Perangin-angin, Esra; Manalu, Ranto Luspen Putra; Br Tarigan, Senania Audina; Ginting, Sri Dinanta Beru (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The background of this problem illustrates a number of challenges faced by students in developing their language skills, and from the results of field observations and the results of exposition texts many language errors were found in grade X students of Raksana Medan Private High School, such as lack of interest in learning, lack of curiosity in language rules, tend to play, not concentrate on learning, not being careful in writing, and students have no limitations in understanding vocabulary. The purpose of this study is to explain (1) To determine errors at the morphological level in the exposition text of class X of Raksana Medan Private High School, (2) To find out language errors in sentences in the exposition text of class X of Raksana Medan Private High School. This research is a qualitative descriptive research using text samples of students of Raksana Medan Private High School. The sampling method used is purposive sampling. The data analysis method used is the Milles and Humberman interactive analysis model which consists of four stages, namely data collection, data validation, data presentation, and sampling techniques. There are still many errors found in writing hyphen sentences, and grade X students of Raksana Medan Private High School still find many errors in morphology such as reduplication errors in writing hyphens, and writing hyphens in sentences on correct reduplication is, such as the next example is Stages. such as theory (Tarigan, 1988:195).Keywords: Language errors, exposition text, morphology.